LOCL-03 INTRATUMORAL DELIVERY OF CONDITIONALLY REPLICATIVE HUMAN ADENOVIRUS 657 EXPRESSING THE IMMUNE CO-STIMULATOR CD40L (CRAD657-CD40L) AS A POTENTIALLY PROMISING TREATMENT FOR RECURRENT PEDIATRIC HIGH GRADE GLIOMA. (5th August 2022) - Webb, Mason; Khatua, Soumen; Thompson, Jill; Yerovi, Maria Chiriboga; Daniels, David; Schartz, Jonathan; Wongthida, Phonphimon; Hopps, Sidney; Barry, Mary; Barry, Michael; Vile, Richard; Diaz, Rosa
Abstract: INTRODUCTION: Malignancies of the central nervous system (CNS) have had largely unchanged survival outcomes despite decades of research. Recently, viral-based therapeutics have shown some benefit for patients with CNS malignancies in early clinical trials. Adenovirus has been demonstrated as safe and is currently being examined in several phase I and II clinical trials. We recently demonstrated that adenovirus expressing CD40L is effective in enhancing survival in murine models of diffuse midline glioma. Therefore, to enhance the tumor specificity of this virotherapy, we hypothesized that by using a novel conditionally replicative adenovirus expressing CD40L, CRAd657-CD40L, we would maintain this survival benefit in multiple murine models for high grade glioma while decreasing off-target toxicity. METHODS: We examined the utility of conditionally replicative adenovirus expressing CD40L in both in vitro and in vivo studies. Human cell lines from diffuse intrinsic pontine glioma (DIPG) and glioblastoma were used to confirm infectivity and CD40L expression, and syngeneic murine models of glioma were evaluated for toxicity and survival following intratumoral injection of a conditionally replicative adenoviral vector. RESULTS: CRAd657-CD40L generated strong expression of CD40L in human in vitro DIPG XIII and U251 cell lines and induced MHCII expression on CD11c+ DC's in U251/DC co-culture. Further, in syngeneic murine models of glioma, conditionally replicative adenoviral treatment significantly reduced toxicity while retaining survival efficacy. CONCLUSIONS: Given these promising results as well as the critical need for novel therapeutics in CNS malignancies, we are now progressing to human trials targeting pediatric HGG, an unmet need in pediatric neuro-oncology. This would be the first-in-human study using CRAd-657-CD40L in pediatric HGG. In this Phase 1 clinical trial, we hypothesize that intratumoral injection of CRAd657-CD40L will cause selective expression of CD40L, increased infiltration of immune cells into the tumor, and safely enhance tumor clearance.